2013
DOI: 10.1629/2048-7754.77
|View full text |Cite
|
Sign up to set email alerts
|

Patron-driven acquisition of journal articles using ReadCube at the University of Utah

Abstract: The University of Utah Library has teamed with a new company, Labtiva, to experiment with a product called ReadCube Access. This product allows the library to provide access to journal articles using a patron-driven acquisition (PDA) mechanism, using a tiered pricing structure based on level and permanence of access. Outcomes of the pilot program and a value analysis are discussed. Overall, the program is deemed a success by the Library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…PDA plans are often executed as a way to realize cost savings, yet England and Anderson acknowledge that "PDA models do not necessarily lead to cost savings, but they do by their very nature forge a strong connection between acquisition and real-world usage, making PDA a potentially attractive model for libraries concerned about maximizing the effective use of their acquisition fund." 25 This finding is consistent with other researchers, such as Dinkins and Schroeder, who have found that PDA selected materials enjoy excellent circulation.…”
Section: Big Dealssupporting
confidence: 91%
“…PDA plans are often executed as a way to realize cost savings, yet England and Anderson acknowledge that "PDA models do not necessarily lead to cost savings, but they do by their very nature forge a strong connection between acquisition and real-world usage, making PDA a potentially attractive model for libraries concerned about maximizing the effective use of their acquisition fund." 25 This finding is consistent with other researchers, such as Dinkins and Schroeder, who have found that PDA selected materials enjoy excellent circulation.…”
Section: Big Dealssupporting
confidence: 91%
“…A striking feature of the project is how little demand exists even with a very low barrier to access -Nature Climate Change costs USD4,985, but had only 12 uses costing $96 (over nine months). It would be interesting to see a comparative study with DeepDyve (England and Anderson, 2013).…”
Section: Document Supplymentioning
confidence: 99%
“…Several articles (England and Jones, 2014;Jones and England, 2014;England and Anderson, 2013;and Weisbrod, 2014) report on the earlier development and piloting of ReadCube Access in libraries. Lancet, (2013),;Fenton (2014) and Hughes (2014)) review ReadCube, the bibliographic management client software.…”
Section: Introductionmentioning
confidence: 99%